The Effects of Dopant Concentration on the Performances of the a-SiOx:H(p)/a-Si:H(i1)/a-Si:H(i2)/Âµc-Si:H(n) Heterojunction Solar Cell - Hamdani, Dadan; Prayogi, Soni; Cahyono, Yoyok; Yudoyono, Gatut; Darminto, Darminto (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
In this work, the imbalances in band gap energy between p-window layer and intrinsic layer (p/i interface) in p-i-n type solar cells to suppress charge recombination adopting with the addition of buffer layer, at p/i interface, namely solar cell structures without buffer (Cell A) and with buffer (Cell B). Using well-practiced AFORS-HET software, performances of Cell A and Cell B structures are evaluated and compared to experimental data. A good agreement between AFORS-HET modelling and experimental data was obtained for Cell A (error = 1.02%) and Cell B (error = 0.07%), respectively. The effects of dopant concentrations of the p-type and n-type were examined with respect to cell B for better performance by analysing the energy band diagram, the electric field distribution, the trapped hole density, the light J-V characteristics, and the external quantum efficiency. The simulated results of an optimised Cell B showed that the highest efficiency of 8.81% (VOC = 1042 mV, JSC = 10.08 mA/cm2, FF = 83.85%) has been obtained for the optimum dopant values of NA = 1.0 x 1019 cm-3 and ND = 1.0 x 1019 cm-3, respectively. A comparison between experimental data and simulation results for Cell B showed that the conversion efficiency can be enhanced from 5.61% to 8.81%, using the optimized values